Jeunesse périphérique en centre-ville : l’exemple de Lyon - Jean-Marc Berthet (Sociétés et Jeunesses en Difficulté)
When peripheral youth comes down town : an example at Lyon. Thinking the city as a resource and mobility as a learning This article presents in a new perspective a research dealing with how suburbs’ youth from the « greater Lyon » practice the centre town, especially rue de la République, the main pedestrian thoroughfare of Lyon’s peninsula, and the shopping centre of La Part-Dieu. What ever do juveniles coming from the so-called difficult neighbourhoods of the greater Lyon when they are not taken in charge either by school or by leisure or sport organisations ? When they stand both outside (in the street, in public space) and inside (in the shopping centre, in the flow of the crowd). To answer those questions, an original method has been employed : observing and following their walking at random on Wednesday and Saturday afternoons over a year long. A vision then comes out : practising space as a series of tests for which strolling becomes a resource (the ability to move oneself on his own way for some, the ability to control behaviours for others) and shows what is at stake both for girls and boys (proximities, chatting up, distance keeping). Thus analysed, the two urban spaces present relatively opposed forms of regulation.